Metabolomics Studies to Assess Biological Functions of Vitamin E Nicotinate - Lucia Marcocci; Yuichiro J. Suzuki (Antioxidants, 2019)
Vitamin E nicotinate (tocopherol nicotinate, tocopheryl nicotinate; TN) is an ester of two vitamins, tocopherol (vitamin E) and niacin (vitamin B3), in which niacin is linked to the hydroxyl group of active vitamin E. This vitamin E ester can be chemically synthesized and is used for supplementation. However, whether TN is formed in the biological system was unclear. Our laboratory previously detected TN in rat heart tissues, and its level was 30-fold lower in a failing heart (Wang et al., PLoS ONE 2017, 12, e0176887). The rat diet used in these experiments contained vitamin E acetate (tocopherol acetate; TA) and niacin separately, but not in the form of TN. Since only TN, but not other forms of vitamin E, was decreased in heart failure, the TN structure may elicit biologic functions independent of serving as a source of active vitamin E antioxidant. To test this hypothesis, the present study performed metabolomics to compare effects of TN on cultured cells to those of TA plus niacin added separately (TA + N). Human vascular smooth muscle cells were treated with TN or with TA + N (100 μM) for 10 min. Metabolite profiles showed that TN and TA + N influenced the cells differentially. TN effectively upregulated various primary fatty acid amides including arachidonoylethanoamine (anandamide/virodhamine) and palmitamide. TN also activated mitogen-activated protein kinases. These results suggest a new biological function of TN to elicit cell signaling.